The Limits of artistic freedom (Discourse of Law and Administration, 2025)
One of the most important manifestations of freedom is the freedom of art. In this sphere, attempts are made to absolutize the freedom of artistic creativity, without noticing any of its limitations. Can an artist really do everything? Does the subjective impression, feeling, view or opinion take precedence over the objective criteria for classifying an object as a work of art? Are there such criteria at all? In fact, the question of the scope of artistic freedom is an issue artificially elevated to a real problem, the victims of which are supposedly great artists deprived of their freedom to create. True art defends itself and does not attack anything by itself. The essence of the act of creation is not to destroy, humiliate or depreciate. Beauty as the fruit of the artist's action is close to good - the Aristotelian goal of all striving, therefore it is far from any form of evil, including offense, contempt, and disrespect.
Keywords: freedom of art; collision of goods; insult to religious feelings; limits of artistic freedom